Reviews - Voeltz, Richard A (Journal of African Cinemas, 2010)
From The Kalahari to Bruce Lee: The Gods must be Crazy I & II , The Hong Kong Sequels and the Globalization of the Bushman
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9qYWMuMi4xLjc2